PEMETAAN RUANG TERBUKA HIJAU DI LINGKUNGAN KAMPUS UNIVERSITAS GADJAH MADA TAHUN 2014 MENGGUNAKAN FOTO UDARA DIGITAL - , SABDO RIYAHADI; , Nur Mohammad Farda, S.Si., M.Cs. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
This study aims to determine the type, distribution and wide open green spaces that exist in the campus of the Gadjah Mada University (UGM) and create a green space map UGM campus environment by utilizing remote sensing data (aerial photographs) and geographic information systems. The method used is a visual interpretation of land cover and land use in the environment by utilizing UGM digital aerial photography in 2012. Besides digital aerial photography, this study also used the base map UGM in the form of vector data for geometric correction of digital aerial photographs and also to obtain other information, such as the limits of land use and building plots. Information on land cover and land use have been obtained, then the condition is checked in the field and reclassified based on the utilization of space. The final results of this study in the form of a map of green open space in the campus of the Gadjah Mada University. The level of accuracy of visual interpretation of land use types in the UGM campus environment using digital aerial photography in this study was 90.38%. The results obtained in this study is known that green open space in the UGM campus, there are several types, namely green space courtyard (49.81 Ha), Green Line Road (6.33 ha), Green Open Space Park and Forest City (10.12 Ha ) and Green Open Space specific functions (2.95 Ha). Overall the green open spaces that exist in the UGM campus based on the results obtained in this study have a percentage of 43% of the entire region mapped UGM campus with an area of 69.28 hectares, the percentage has met the minimum standards by law Republic of Indonesia No. 26 of 2007, which amounted to 30% of the area of a region.